The Status of Erwinia amylovora in the Former Yugoslav Republics over the Past Two Decades (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Erwinia amylovora, the causal agent of fire blight (FB) on fruit trees and ornamental plants, rapidly spread across eastern Mediterranean countries in the early 1980s. This quarantine bacterium arrived in the southern parts of the former Yugoslavia (now FYR Macedonia) from Greece in 1986. Based on symptoms, and isolation and identification data, it was concluded that Erwinia amylovora was the causal agent of pear drying in Macedonia (1989). It was the first experimental confirmation of a presence of E. amylovora in the territory of the former Yugoslavia. The presence of E. amylovora was also proved in Serbia that same year. In Bosnia and Herzegovina, FB was detected during 1990. Based on an official report filed with the Federal Ministry of Agriculture in Belgrade, the presence of E. amylovora in  Yugoslavia was confirmed (EPPO – Reporting Service, 1991). Therefore, the presence of the bacterium E. amylovora in the territory of Yugoslavia was officially confirmed in 1990. In Croatia, FB was first observed in villages near the border on Serbia in 1995. In Montenegro, FB was first detected in 1996. In Slovenia, FB appeared as late as in 2001. E. amylovora is now present on 10 hosts (pear, wild pear, apple, quince, medlar, mountainash, hawthorn, firethorn, cotoneaster and Japanese quince) in the territory of the former Yugoslav republics. Based on literature data, losses caused by FB in the former Yugoslav republics in the period 1989-1992 were estimated at about 12,000,000 DEM (mostly in Macedonia) and in the period 1992-1996 at 6,000,000 DEM. Total damage in a more recent epiphytotic year in Slovenia (2003) was estimated at about 474,200 EUR. Conventional and up-to-date rapid methods (PCR, ELISA and IF, BIOLOG and API System, FAME and SDS-PAGE) have been used to identify E. amylovora. Mainly preventive measures have been used to control E. amylovora in the former Yugoslav republics. Spraying with copper products has been practiced during the dormant period and in early spring. In rare cases, spraying has been done at the flowering stage (MARYBLYT), but the problem is that no synthetic bactericides are available on the market. When symptoms occur, only mechanical measures are being applied.
Keywords: Former Yugoslavia; Control; Distribution; Occurrence; Erwinia amylovora